Online interaction learning: A way towards sustainability and buoyant EFL students - Seyedhamed Sadoughvanini; Hamed Ghaemi (Australian Journal of Applied Linguistics)
The ability of students to deal with common academic difficulties is referred to as academic buoyancy. It can also be described as the capacity of students over obstacles and difficulties that are typical of the everyday school experience. The purpose of this research was to examine the connections between the academic buoyancy of Iranian university-level EFL students and their online interaction learning model. Online interaction learning seems to be a strong predictor of academic buoyancy. Academic buoyancy surveys and the online interaction learning model were given to students majoring in English translation and teaching English as a second, third, and final year of college. Both structural equation modeling and correlational studies found a statistically significant association between academic buoyancy, online interaction learning, and all of their components. The best predictors of academic buoyancy, according to regression analysis, were the components of course material and instructor performance. Taken together, the findings add to what is widely accepted about the online engagement tendency of university students and sheds light on the academic buoyancy constructs in higher education. However, more research on the role of buoyancy in relation to achievement and online tactics to increase individual students’ achievement and overall online interaction learning model is warranted based on the findings of the present study.